DUPLICATION IN INDONESIAN JOURNAL ARTICLE: QUALITY ANALYSIS - Ekawati Marlina; Retno Asihanti Setiorini; Kamariah Tambunan (Pusbindiklat - LIPI, 2015)
There are several cases of duplicate articles in Indonesian scientific journal. This study provide inputs tothe journal publisher in Indonesia to prevent duplication. This paper conducted analysis of quality articles andjournals, data obtained from the Indonesian Scientific Journal Database (ISJD) and printed journals in PDIILIPI. The results show (1) the duplication are written by the same author, but published in different journals, in thesame or different year; (2) articles published in the same journal but in different volume; (3) articles from a similarresearch team, but published as sole author under the name of each member of the group. Most journals alreadyinclude a requirement that the article submitted has not been published in other journals. This paper suggests inorder to avoid duplication, each journal should add the prerequisite, such as authors should not submit the articleto other publishers before the selection process has been completed. In addition, to address duplication, whilethe selection is in process, publisher should conduct a benchmarking script analysis to search articles that havebeen published. ISJD, is a database for comparing articles and managed by PDII LIPI. Currently, ISJD alreadymanages more than 5,000 journals with more than 140,000 articles. This study is expected to provide input to thejournal publisher in Indonesia, so there is no duplication of publication of the article.